1964
DOI: 10.1007/bf01894936
|View full text |Cite
|
Sign up to set email alerts
|

Zur Entstehung und Feinstruktur skulpturierter Hoftüpfel bei Leguminosen

Abstract: EinleitnngMehrere Laubholzarten, insbesondere der tropischen Leguminosen, zeiehnen sieh dureh eine auff~llige Erseheinungsform der intervascularen Hoftfipfel aus, die Ms ,verzierte" oder skulpturierte Tfipfel bezeiehnet werden. Die Verzierung besteht aus feinen Erhebungen, die an versehiedenen Stellen der Tfipfelwandung~ sowie auch auf der Gef~13wand vorkommen. BAIL]~u (1932, 1933) hat diese Strukturen erstmMs n~her untersueht und hierffir die Bezeiehnung ,,vestured pits" eingef~ihrt. Die liehtoptisehen Unter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

1964
1964
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
13
0
3
Order By: Relevance
“…In general, the overall habitat preferences of plants with vestures are the tropics and subtropics rather than the cool temperate to arctic or alpine floras, as has been suggested previously (Schmid and Machado 1964;Zweypfenning 1978). We therefore suggest that vestured pits have a positive adaptive significance for water transport in woody plants that develop high negative pressures in their xylem.…”
Section: Ecological Trends In the Distribution Of Vestured Pitsmentioning
confidence: 53%
See 1 more Smart Citation
“…In general, the overall habitat preferences of plants with vestures are the tropics and subtropics rather than the cool temperate to arctic or alpine floras, as has been suggested previously (Schmid and Machado 1964;Zweypfenning 1978). We therefore suggest that vestured pits have a positive adaptive significance for water transport in woody plants that develop high negative pressures in their xylem.…”
Section: Ecological Trends In the Distribution Of Vestured Pitsmentioning
confidence: 53%
“…With the advent of the electron microscope, the micromorphology and distribution of vestured pits could be studied in much greater detail during the 1960s and 1970s (Cô té and Day 1962;Schmid and Machado 1964;Meylan and Butterfield 1974;Ohtani and Ishida 1976;Van Vliet 1978). Mapping the presence of vestured pits onto recent angiosperm phylogenies based on molecular sequence data has shown that the feature must be under strong genetic control and is diagnostic for all taxa of a number of clades (Jansen et al 1998(Jansen et al , 2000a(Jansen et al , 2001Jansen and Smets 2000;Jørgensen 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In E. regnans they appeared to be even more clearly analogous to the warts ( Figure 8). Cote and Day (1962) and Wardrop et al (1963) considered that there was indeed an analogy between warts and vestures, while Schmid and Machado (1964) and Schmid (1965) have suggested that there is a fundamental difference in their formation. From these present observations, especially with E. regnans, their general structural appearance is undeniably similar (see also Scurfield and Silva 1970).…”
Section: Observations and Discussionmentioning
confidence: 96%
“…More pertinent is the report of structures comparable to the verrucae of Cercidium in another genus ofFabaceae, Prosopis (Castro 1988). Warts on vessel walls of certain Fabaceae mentioned by Schmid and Machado (1964) are smaller in size. The diversity of verrucae in Cercidium is surprising, and is summarized under Taxonomic Conclusions below.…”
Section: Morphological Conclusionmentioning
confidence: 97%